2014
DOI: 10.1186/1471-2296-15-89
|View full text |Cite
|
Sign up to set email alerts
|

General practice and ethnicity: an experimental study of doctoring

Abstract: BackgroundThere is extensive evidence of health inequality across ethnic groups. Inequity is a complex social phenomenon involving several underlying factors, including ethnic discrimination. In the field of health care, it has been established that ethnic discrimination stems partially from bias or prejudice on the part of doctors. Indeed, it has been hypothesized that patient ethnicity may affect doctors’ social cognition, thus modifying their social interactions and decision-making processes. General practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…We therefore conclude that there is a significant association between migration status and medical decisions. These differences are consistent with previous studies that also found that medical decisions were affected by a patient’s ethnic background (Centola et al, 2021 ; Lepièce et al, 2014 ). Indeed, providers’ biases have already led to the unsafe undertreatment of migrant patients (Centola et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We therefore conclude that there is a significant association between migration status and medical decisions. These differences are consistent with previous studies that also found that medical decisions were affected by a patient’s ethnic background (Centola et al, 2021 ; Lepièce et al, 2014 ). Indeed, providers’ biases have already led to the unsafe undertreatment of migrant patients (Centola et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…First, we asked them what type of treatment they would prescribe, providing three different options: non-medical treatment, medical treatment, or a combination of both. Then, we asked those who had prescribed medical treatment or a combination of both if they would prescribe benzodiazepines (i.e., hypnotics, sedatives, and anxiolytics), because literature shows that GPs prescribe drugs more often to ethnic minority patients (Lepièce et al, 2014 ). Finally, we surveyed how likely the GP respondents were to refer the patient, also using the 4-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies assessed more than one race. One study [ 82 ] assessed the biases of local (European) general practitioners against individuals with migrant status compared to local people using a foreign (Moroccan) vs. a typical local (Belgian) name. No study investigated bias against Asian people or people from other racial or ethnic backgrounds.…”
Section: Resultsmentioning
confidence: 99%